Effects of fuel properties and aerodynamic breakup on spray under flash boiling conditions. (5th January 2022) - Zhao, Weihua; Yan, Junhao; Gao, Suya; Lee, Timothy H.; Li, Xiangrong
Highlights: Sprays of four single component fuels under flash boiling conditions were studied. Spray collapses at R p of 0.28 for isooctane, hexane and ethanol, and 0.18 for pentane. Ethanol has relatively larger near-field angle, far-field angle and SMD. Aerodynamic breakup still plays an important role under low flash boiling conditions. Isooctane, hexane and pentane under R p of 0.28 show a similar SMD value of 10 µm. Abstract: The main purpose of this work is to conduct detailed comparisons of spray behavior among four important components of gasoline and to investigate the effects of fuel properties and aerodynamic breakup on spray behavior under flash boiling conditions. Isooctane, hexane, pentane, and ethanol were used as test fuels. Pressure ratio ( R p ) was used as an indicator for the superheated degree and varied from 0.14 to 1.1 by adjusting the ambient pressure. Both Diffused Backlight Imaging (DBI) and Phase Doppler Anemometry (PDA) measurements were used to obtain macroscopic and microscopic characteristics of sprays. Four dimensionless numbers were used to evaluate the aerodynamic breakup processes. The results showed that as the reduction of R p, the flash boiling intensity increased, leading to dramatic spray morphology changes and smaller droplet size, regardless of fuel type. Spray plumes merged into the spray center when lowering R p from 1.0. Spray collapsed at an R p of 0.28 for isooctane, hexane, and ethanol, and at an R p of 0.18 for pentane. Fuel properties also had significant effects on spray behaviors. Spray with pentane had the smallest penetration length, and a dramatic far-field angle reduction was observed at R p between 0.2 and 0.4, due to its higher vapor pressure and lower latent heat of vaporization. Under the same R p, ethanol sprays had relatively larger near-field angles, far-field angles, and Sauter mean diameter (SMD), due to its high latent heat of vaporization. All the dimensionless numbers showed that the spray with pentane had the largest aerodynamic breakup intensity, followed by hexane and isooctane, while ethanol had the lowest aerodynamic breakup intensity under the tested conditions. Aerodynamic breakup still played an important role under low flash boiling intensity conditions ( R p over 0.8). Microscopic results showed that SMD of isooctane, hexane, and pentane under an R p of 0.28 had a similar value of 10 µm.